APPROACHING DEVELOPMENT IN LOGISTIC INFORMATION SYSTEMS - Buys, Louis F (The South African Journal of Industrial Engineering, 2012)
The introduction of technology into modern defence necessitates integrated computerized information systems to render effective and efficient logistic support. Traditional information system development does not ensure attainment of use and time scale requirements in the continuously developing environment of logistics. This paper describes current approaches to the development of logistic information systems.